2021
DOI: 10.1186/s12877-021-02515-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent eosinopenia is associated with in-hospital mortality among older patients: unexpected prognostic value of a revisited biomarker

Abstract: Introduction Infection is one of the major causes of mortality and morbidity in older adults. Available biomarkers are not associated with prognosis in older patients. This study aimed to analyze the value of eosinopenia (eosinophil count< 100/mm3) as a prognosis marker among older patients with suspected or confirmed bacterial infection. Methods A retrospective study was performed from 1 January to 31 December 2018 among patients in a geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This result correlates with a prospective study (96 patients, mean age (SD): 64 [21] years old)), in which patients suffering from bacterial infection with eosinophil count < 0.01 G/L had a faster eosinophil normalization than CRP [19]. More recently, a retrospective study including 197 patients of an age closer to that ouf our study (mean age (SD): 89.6 (5.7)), found that persistent eosinophil count < 0.1 G/L between day 2 and day 4, was associated with in-hospital mortality (HR: 8.9 [3.46-22.9]) [30]. However, eosinophil count < 0.04 G/L combined with WBC > 10 G/L has been studied in an internal medicine ward on 138 patients aged of 71.8 (29.9) y/o, and had high specificity (100%) with a sensitivity of 64% [17].This result was not confirmed in our study, probably because WBC > 10 G/L and a CRP > 20 mg were inclusion criteria and included patients were older (88.8 (5.6) y/o compared to 71.8 y/o).…”
Section: Discussionsupporting
confidence: 67%
“…This result correlates with a prospective study (96 patients, mean age (SD): 64 [21] years old)), in which patients suffering from bacterial infection with eosinophil count < 0.01 G/L had a faster eosinophil normalization than CRP [19]. More recently, a retrospective study including 197 patients of an age closer to that ouf our study (mean age (SD): 89.6 (5.7)), found that persistent eosinophil count < 0.1 G/L between day 2 and day 4, was associated with in-hospital mortality (HR: 8.9 [3.46-22.9]) [30]. However, eosinophil count < 0.04 G/L combined with WBC > 10 G/L has been studied in an internal medicine ward on 138 patients aged of 71.8 (29.9) y/o, and had high specificity (100%) with a sensitivity of 64% [17].This result was not confirmed in our study, probably because WBC > 10 G/L and a CRP > 20 mg were inclusion criteria and included patients were older (88.8 (5.6) y/o compared to 71.8 y/o).…”
Section: Discussionsupporting
confidence: 67%
“…In human medicine, eosinopenia is considered a reliable prognostic marker in acute ischemic stroke [ 46 ], coronavirus [ 47 ], urticaria [ 48 ], non-cardiac vascular surgery [ 49 ] and acute myocardial infarction [ 50 ]. There is also an association between persistent eosinopenia and high mortality in aged hospitalized patients [ 51 ]. However, despite the extensive bibliography that exists in human medicine, to the authors’ knowledge, there are no studies on eosinopenia as a prognostic marker in horses.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the SARS-CoV‑2 pandemic, several studies recognized the potential role of eosinophil count in disease prognosis, mostly associating eosinopenia with poor outcomes [ 25 28 ]. Additionally, eosinopenia has also been associated with poor outcomes in patients with bacterial infections [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%